A decision tree approach based on BOCR for minimizing criteria in requirements prioritization - Tan, Amelia; Rozlina, Mohamed (Institute of Advanced Engineering and Science, 2023)
The requirements selection in the development of a software mostly requires a set of criteria. Determining the criteria used is often confusing because of the many criteria that must match with the characteristics of the project. This study introduces how to classify criteria based on benefits, opportunities, costs, risks (BOCR) to make the requirements prioritization process scalable. Project context characteristics and stakeholder perspectives are essential points discussed in this study because they are crucial in the requirements prioritization process. The criteria obtained from the literature review were followed by a survey to determine the importance of the criteria and their grouping in the BOCR using the decision tree method. There are 38 criteria and are grouped into four categories. There are two very significant criteria with a high level of importance, namely business value and stakeholder satisfaction. A decision tree based on BOCR can be used to classify the criteria for requirements prioritization. This research contributes to assisting software developers in finding and determining the criteria operated during the prioritization of requirements. Additionally, it is important to consider the project context and the collaboration the client and developer when prioritizing requirements.